Axiology or Teleology as the Basis of State–Church Law Relations in The Third Republic of Poland? - Bartczak, Adam (Acta Universitatis Lodziensis. Folia Iuridica, 2024)
The article addresses the issue of the basis of modern relations between the state and the Catholic Church on legal grounds. Two independent communities, along with their laws, must coexist in one territory. The only chance for success is dialogue and mutual understanding. The purpose of the article was to try to assess what lies at the heart of this relationship. Is it axiology understood as value or perhaps teleology read in the perspective of a specific purpose.